The observer effect in graphene oxide – How the standard measurements affect the chemical and electronic structure. (July 2016) - Rogala, M.; Dabrowski, P.; Kowalczyk, P.J.; Wlasny, I.; Kozlowski, W.; Busiakiewicz, A.; Karaduman, I.; Lipinska, L.; Baranowski, J.M.; Klusek, Z.
Abstract: Complementary research is presented to prove that graphene oxide is highly sensitive to unintended modifications during standard measurements. X-ray photoelectron spectroscopy, Raman spectroscopy and atomic force microscopy current imaging is used to characterize graphene oxide samples. Conducted experiment indicated that the investigated material can be easily modified during characterization. Such observer effect has influence on chemical and electronic structure of graphene oxide. The focus is put on the possibility of evaluating the reliability of experimental results. It is proposed that, when dealing with graphene oxide, constant verification of measurement procedure influence is required. The compromise should be achieved between the quality of experimental data and its correspondence to the real properties of the sample prior investigation. However, this can be done only when researchers are aware of the sensitivity of the graphene oxide structure for applied observation.